Corporate Social Responsibility Disclosure and Company Performance: The Moderating Role of CEO Characteristics and Institutional Ownership - Muhammad Ahnaf Ammar Qushoyyi; Irwan Trinugroho (Postgraduate Program Merdeka University, 2024)
This study aims to examine the effect of corporate social responsibility disclosure (CSRD) on company performance with CEO characteristics and institutional ownership as moderating variables. This research is quantitative research using a sample of LQ45 index companies listed on the Indonesia Stock Exchange. This research data collection method uses secondary data sourced from company Annual Reports obtained from the Indonesia Stock Exchange (BEI). This model answers the objectives of this research based on a selected sample of 112 observations from 28 companies between 2019-2022. The research results show that corporate social responsibility disclosure (CSRD) influences company performance, while profitability influences company value. This research also shows that corporate social responsibility disclosure (CSRD) on company performance cannot be moderated by CEO tenure, while corporate social responsibility disclosure (CSRD) on company performance can be moderated by institutional ownership.DOI: https://doi.org/10.26905/afr.v7i2.12800Â